PELATIHAN LITERASI KEUANGAN DALAM MENINGKATKAN PENDAPATAN IBU GURU DAN WALI MURID - Yunarni, Baiq Reinelda Tri; Eikman, Alfian; Juriani, Juriani; Chairunissa, Ariffina; Kawsar, Rizqa Hikmatul (Jurnal Abdimas Sangkabira, 2024)
Financial literacy training is a strategic effort to enhance understanding and skills in managing finances, especially for teachers and parents who play a crucial role in family financial management. This community service program aims to equip participants with basic financial literacy knowledge, including financial planning, household budget management, debt management, and simple investments. This training also develops small entrepreneurship skills that can be conducted from home, such as utilizing digital technology for product marketing. The training program will be held on June 4, 2024, to improve financial management skills. The community service activities begin with a needs assessment through surveys and interviews, followed by preparing relevant training materials. Implementation is carried out through several theory and practice sessions that include simulations of financial management and small business operations. To ensure the sustainability of the training results, intensive monitoring and post-training assistance are conducted, along with an evaluation of the participants’ application of financial literacy. The outcomes of this program are expected to improve the financial literacy of teachers and parents, enabling them to manage their family finances more wisely and increase their income through sustainable small businesses. This training is also anticipated to reduce economic disparities within the school environment and strengthen family economic resilience.